HUBUNGAN ANTARA KECERDASAN INTRAPERSONAL DENGAN KEMANDIRIAN ANAK USIA 5-6 TAHUN DI RA MADINATUSSALAM KEC. PERCUT SEI TUAN - Hamidah Saroh; Khadijah Khadijah; Arlina Sirait (Universitas Islam Negeri Sumatera Utara, 2019)
This study aims to analyze the correlation between interpersonal intelligence with indepence of students aged 5-6 old in RA Madinatussalam, Percut Sei Tuan District. This study is a quantitative correlational research that aims to examine correlations through numbers. Determination of the sample of researchers used total sampling technique because the number of samples was less than 30, namely 24 children aged 5-6 old in RA Madinatussalam. Data analysis was performed by testing the prerequisites for the analysis of the validity test, which is that all data are valid because r count> r table. Reliability test results are variable one 0.954 and variable two 0.937 with the acquisition of a score greater than 0.6, it can be concluded that the test is reliable. The normality test results with the Sig value. (2-tailed) of 0,200 greater than the significance level, which is 0,05. This means the assumption of normality. And the results of hypothesis testing using Pearson product moment correlation test with a value of 0.776 which is included in the interval of the strong relationship category. If r count (0.776)> rtable (0.423) then the item is said to be valid or Ho is rejected, meaning there is a significant relationship between intrapersonal intelligence and the independence of children aged 5-6 old.